Necessary optimality conditions for abnormal abstract problems with general constraints - Fernando Lobo Pereira (2008)
Here, we derive second-order necessary conditions of optimality for an abstract optimization problem with equality and inequality constraints and constraints in the form of an inclusion into a given closed set. An important feature is that our optimality conditions dispense with any a priori normality assumptions, such as Robinson's constraint qualification, and remain informative even for abnormal points.